Dimensi Sosio-Paedagogis Dalam Konstruksi “Umma Bodomaroto” - Djawa, Maya; Luji, Daud Saleh (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article explores a study on the socio-pedagogical dimension in the construction of um’ma, the traditional house of the local Sumba Tribe in Kampong Bodomaroto, West Sumba. Several dimensions were analyzed regarding the local Bodomaroto’s perspectives on the meaning and functions of um’ma as a traditional house. Firstly, the Bodomaroto community perceives um’ma as a vessel that encapsulates the profound essence of Bodomaroto and its people. They view um’ma Bodomaroto as a representation of their collective identity as human beings. Secondly, the functions of um’ma are observed through its conceptualization and its connection to cosmology, which can be divided into two parts: horizontal and vertical space. This cosmology is associated with the human body. Um’ma Bodomaroto embodies physical and social entities. Thirdly, um’ma Bodomaroto holds socio-pedagogical values that are translated into moral education. The moral education encompasses several aspects: (1) nurturing children through rabuka and lado, emphasizing parental responsibilities, (2) fostering an understanding of the economy through kotatu and wasu patunu, (3) promoting respect for the living environment through padalu, (4) maintaining a balance of responsibilities through the four pillars, (5) cultivating harmony and fellowship through kogola, (6) assuming responsibility for the well-being of the entire household through wo’o letara, (7) respecting the body through muat alang representation, and (8) adhering to firm and focused principles through kaluota. These eight moral concepts serve as guiding principles for community education. These concepts are integrated into the education system, aligning with the philosophy of liberating education put forth by Paulo Freire. According to Freire, education comprises three crucial elements that are interrelated with the meaning and function of um’ma.